Pengaruh Kecerdasan Emosional Terhadap Hasil Belajar Pendidikan Jasmani pada Masa Pandemi - Ali Mardius; Enjoni Enjoni; Al Busyra Fuadi (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
Abstract This study aims to determine the effect of Emotional Intelligence on physical education learning outcomes during the pandemic. This type of quantitative research uses a correlation research design with a causal associative method. The population in this study amounted to 62 people. The sampling technique used total sampling technique, which is a sampling technique that provides equal opportunities for each element/member of the population to be selected as a member of the sample, while the number of samples in this study was 62 people. Data were collected using a questionnaire. Data were analyzed by multiple regression of two predictors. Based on the results of data analysis shows that: Variable emotional intelligence has a significant effect on learning outcomes of physical education. This means that the higher the emotional intelligence, the better the physical education learning outcomes. Keywords: Emotional Intelligence, Learning Motivation and Learning Outcomes